Digital Public Services and Community Access: Effectiveness of the Digital Village Application (DIGIDES) in Waiheru Village, Ambon City - Galih Dito Kuncoro; pieter sammy Soselisa; Ivonny Yeany Rahanra (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study analyzes the effectiveness of the Digital Village Application (DIGIDES) in improving administrative public services, service access, citizen participation, and community satisfaction in Waiheru Village, Baguala District, Ambon City. Methodology: This study employed a descriptive qualitative approach. Data were collected through direct observation, semi-structured interviews, and documentation involving village officials, the application operator, and community beneficiaries. Data were analyzed through reduction, display, verification, and interpretation based on public service effectiveness indicators. Main Findings: The findings show that DIGIDES has improved service accuracy, administrative efficiency, population data management, and transparency for village officials and digitally capable residents. However, its community-level use remains limited because of uneven digital literacy, inadequate socialization, operator dependency, and unstable internet connectivity. These constraints affect service access, restrict citizen participation, and create uneven changes in village governance: residents who are digitally literate benefit from faster services, while older residents, low-literacy groups, and people with limited internet access remain dependent on face-to-face assistance. Novelty/Originality of this study: This study combines effectiveness analysis with a social impact perspective by treating village digitalization not merely as a technological innovation but as a public service process that shapes inclusion, access, participation, and relations between village officials and citizens.